Sistema de gestión del servicio al cliente de la Panadería California del cantón Vinces, periodo 2023. - Gómez Fernández, Danilo Samuel (2024)
The following case study, whose theme is based on the Customer Service Management System of the California bakery in the Vinces canton, period 2023, aims to analyze aspects related to the levels of customer satisfaction and loyalty. The applied research methodology is descriptive that helped in the analysis and collection of data in the information, it is also focused on the analytical method that served to collect data provided by the community, likewise the survey was implemented as a technique, which was directed to the urban population of the Vinces canton, whose sample was 380 people, the instrument used to obtain the information was the questionnaire established using the Google Forms tool, with a content of 9 closed questions, with this information it was possible to determine that the attention that employees provide is framed between almost good and average, on the other hand, respondents stated that the business must have a diversity of products and excellent quality. On the other hand, when consulting another group, they indicated that they would like the business to provide other additional services such as home delivery, promotion and discount programs, among others. Finally, other people surveyed stated that they would like the establishment to have improvements, such as reducing waiting time when making purchases and ensuring that the system for handling complaints and problems is efficient and timely when they arise, through these alternatives of modifications made on time, they are essential for the business to improve, differentiate yourself from the competition, increase your sales, and position yourself in the market.